2014
DOI: 10.1111/ijd.12680
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Barthel index, activities of daily living, in dermatologic surgery in patients aged 80 years and older

Abstract: Activities of daily living were not significantly affected in patients aged 80 years and older, after dermatologic surgery for NMSC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 9 publications
1
14
1
2
Order By: Relevance
“…Furthermore, most of the studies involving postoperative complication rate show no difference in the occurrence of complications between age groups. 12,14,[29][30][31][32] On the contrary, Mueller et al 20 found that patients >70 years of age were 2.7 times more likely to develop postoperative wound healing disorders compared with younger patients (P = 0.03) and Pascual et al 33 describe more haemorrhagic complications in the higher age group (P = 0.04). On the other hand, an age of <60 years was found to be associated with a higher risk of postoperative complications by Sclafani et al 32 (P = 0.01) ( Table 1).…”
Section: Effect Of Age On Treatment Outcomes Of Common Treatment Modamentioning
confidence: 99%
“…Furthermore, most of the studies involving postoperative complication rate show no difference in the occurrence of complications between age groups. 12,14,[29][30][31][32] On the contrary, Mueller et al 20 found that patients >70 years of age were 2.7 times more likely to develop postoperative wound healing disorders compared with younger patients (P = 0.03) and Pascual et al 33 describe more haemorrhagic complications in the higher age group (P = 0.04). On the other hand, an age of <60 years was found to be associated with a higher risk of postoperative complications by Sclafani et al 32 (P = 0.01) ( Table 1).…”
Section: Effect Of Age On Treatment Outcomes Of Common Treatment Modamentioning
confidence: 99%
“…Moreover, patients aged 60 years or older, patients with tumours larger than 10 cm, and patients with malignant tumours required a longer rehabilitation period; these results were consistent with past reports on cancers other than musculoskeletal tumours. 21,22) Although soft tissue tumours required a longer rehabilitation period than bone tumours, there was no reduction in the Barthel Index at the end of rehabilitation. One reason for this result may be complications, such as the necessity for functional reconstruction during surgery, failure of sutures, or infection.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for a low post-rehabilitation Barthel Index were malignant tumours and tumours larger than 10 cm; these findings were also consistent with past reports on other types of cancers. 21,22) In the current study, we also examined the relationship between the post-rehabilitation Barthel Index and the Musculoskeletal Tumour Society Score/Toronto Extremity Salvage Score were developed as disease-specific postoperative functional evaluation scales for musculoskeletal tumours. 23,24) The Musculoskeletal Tumour Society Score is an easily applied, highly reproducible, and versatile scale that is aimed at evaluating functional impairment and decreased functional ability after treatment of musculoskeletal tumours.…”
Section: Discussionmentioning
confidence: 99%
“…The Barthel Index (BI) is a 10-item instrument measuring disability in terms of a person's level of functional independence in personal ADL (8). BI comprises 10 ADL, each of which is graded as 0, 5, or 10 with a maximum total score of 100 (9). A higher score means better capacity to perform daily living activities (8,9).…”
Section: Measurement Instrumentsmentioning
confidence: 99%
“…BI comprises 10 ADL, each of which is graded as 0, 5, or 10 with a maximum total score of 100 (9). A higher score means better capacity to perform daily living activities (8,9). IADL were measured by employing the Instrumental Activities of Daily Living Scale (IADL) (5), which includes a range of higher-level activities that are considered to address the older adult's capacity to interact with his or her community (10).…”
Section: Measurement Instrumentsmentioning
confidence: 99%